2017
DOI: 10.11124/jbisrir-2016-003119
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Manchester Triage System on time to treatment in the emergency department: a systematic review protocol

Abstract: The review aims to find the best available evidence on the effectiveness of the Manchester Triage System on time to treatment in the emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…It consists of 52 units based on the main symptoms [16]. The key parameters, such as threat to life, pain, or consciousness disorder are defined for each of these block diagrams [26][27][28]. This sorting system uses certain important indicators as discriminators in the current flowchart [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It consists of 52 units based on the main symptoms [16]. The key parameters, such as threat to life, pain, or consciousness disorder are defined for each of these block diagrams [26][27][28]. This sorting system uses certain important indicators as discriminators in the current flowchart [28].…”
Section: Resultsmentioning
confidence: 99%
“…The key parameters, such as threat to life, pain, or consciousness disorder are defined for each of these block diagrams [26][27][28]. This sorting system uses certain important indicators as discriminators in the current flowchart [28]. The effectiveness of this system was demonstrated in a 2012 retrospective cohort study aimed at assessment of the MTS accuracy at determining risks and priorities for the patient care within 24 hours of admission to emergency departments, which indicated that half of 139,000 patients were triaged within the recommended time (2-20 minutes), 88.4% of patients were not hospitalized, whereas 11.4% were hospitalized, and just 0.2% of cases were fatal [6,29].…”
Section: Resultsmentioning
confidence: 99%
“…In demonstrating the validity of the MTS, this study's findings are consistent with those of numerous other studies in various settings and countries. The MTS has been observed to have particularly good performance for adult and paediatric patients 5,12,13 , although Zachariasse et al 14 found frequent incorrect classifications of children.…”
Section: Discussionmentioning
confidence: 99%
“…The result of applying the MTS to an incoming patient is a deterministic colour-code that will identify patients at higher risk for deterioration and assign them to be cared for by medical personnel more quickly than those with lower risk [3].…”
Section: Introductionmentioning
confidence: 99%